The Effect Of Senior Elastic Band Exercise on Increasing Muscle Strength of The Elderly in Sandik Village, Meninting Health Center Working Area, West Lombok District - Eka Rudy Purwana; Zulkifli Zulkifli; Aan Dwi Sentana; Dita Dara Pertiwi; Herni Sulastien (Fakultas Ilmu Kesehatan Universitas Nahdlatul Wathan Mataram, 2023)
Background: Elderly is the final stage of the aging process which experiences a decrease in organ function, one of which is a decrease in physical condition in the form of a decrease in muscle mass which causes a decrease in muscle strength, thus affecting daily activities. So physical exercise is needed, namely the Senior Elastic Band Exercise . Research Objective: to determine the effect of the Senior Elastic Band Exercise on increasing muscle strength in the elderly. Method: Pre-experimental research design, one group pretest posttest . The population is elderly people who experience decreased muscle strength aged 60-69 years in Sandik Village, the working area of the Meninting Health Center, West Lombok District with a population of 804. Samples were taken using purposive sampling of 20. Data collection used the MMT observation sheet and analysis used the Wilcoxon test. Results: Elderly muscle strength before intervention was given: shoulder at grade 4 = 100%, hip at grade 4 = 60%, and knee grade 4 = 55%. Elderly muscle strength after being given intervention : shoulders at grade 5 = 65% while hip muscle strength at grade 4 = 50% and knee grade 4 = 65%. The results of the Wilcoxon statistical test showed p-value = 0.000 < α 0.05, which means that H 0 was rejected, which means there is an influence of the Senior Elastic Band Exercise on the muscle strength of the elderly. Conclusion: Senior Elastic Band Exercise increases muscle strength in elderly people who experience decreased muscle strength. Suggestion: Can be used as an intervention to increase muscle strength in elderly people who experience decreased muscle strength.